Social values and health systems in health policy and systems research: a mixed-method systematic review and evidence map - Whyle, Eleanor; Olivier, Jill (Health policy and planning, 2020)
Abstract Because health systems are conceptualized as social systems, embedded in social contexts and shaped by human agency, values are a key factor in health system change. As such, health systems software—including values, norms, ideas and relationships—is considered a foundational focus of the field of health policy and systems research (HPSR). A substantive evidence-base exploring the influence of software factors on system functioning has developed but remains fragmented, with a lack of conceptual clarity and theoretical coherence. This is especially true for work on ‘social values’ within health systems—for which there is currently no substantive review available. This study reports on a systematic mixed-methods evidence mapping review on social values within HPSR. The study reaffirms the centrality of social values within HPSR and highlights significant evidence gaps. Research on social values in low- and middle-income country contexts is exceedingly rare (and mostly produced by authors in high-income countries), particularly within the limited body of empirical studies on the subject. In addition, few HPS researchers are drawing on available social science methodologies that would enable more in-depth empirical work on social values. This combination (over-representation of high-income country perspectives and little empirical work) suggests that the field of HPSR is at risk of developing theoretical foundations that are not supported by empirical evidence nor broadly generalizable. Strategies for future work on social values in HPSR are suggested, including: countering pervasive ideas about research hierarchies that prize positivist paradigms and systems hardware-focused studies as more rigorous and relevant to policy-makers; utilizing available social science theories and methodologies; conceptual development to build common framings of key concepts to guide future research, founded on quality empirical research from diverse contexts; and using empirical evidence to inform the development of operationalizable frameworks that will support rigorous future research on social values in health systems.